ADHD Symptoms in Adults and Time Perspectives – Findings From a Czech National Sample - Weissenberger, Simon; Děchtěrenko, Filip; Klicperova-Baker, Martina; Vňuková, Martina; Zimbardo, Phillip; Raboch, Jiří; Anders, Martin; Braaten, Ellen; Ptáček, Radek (Frontiers in Psychology, 2020)
ADHD is one of the most common neurodevelopmental disorders, affecting individuals in all stages of their lives and leading to a variety of negative quality of life outcomes. The disorder is associated with marked differences related to time perception and time perspectives, and this area of research is currently becoming more prominent and gaining ground in showing new aspects of ADHD that were considered secondary (i.e. time perception differences, affective differences). In this study we looked at ADHD symptoms in adults, correlated lifestyles and time perspectives as defined by the Zimbardo Time Perspective Inventory (ZTPI). The ZTPI is a useful standardized scale to measure one’s time perspective anchoring in the categories of past positive, past negative, present fatalistic, present hedonistic and future oriented. This is the first study on adult ADHD and time perspectives conducted in the Czech Republic.